Perlindungan Terhadap Hak-Hak Kelompok Minoritas Di Indonesia Dalam Mewujudkan EQUALITY BEFORE THE LAW - Ika Fitriana (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2021)
After overthrowing the bloody New Order system which was marked by various human rights crimes for nearly 32 years, the reform system supported the rule of law and realized democratization in all areas of life without respecting human rights. discrimination. But what happened on the other hand actually led to acts of violence and discrimination against minority groups during the reformation period. The difference is, violence in this government is not only carried out by state authorities, but by a group of people with certain identities who appear to present the oligarchic power in the power of the legitimate Republic. Therefore, we need to know what legal protection has been given by the state to Indonesian minority groups. This search uses secondary (special) data, prescriptive legal methods carried out through literature studies that have searched for laws, research results, scientific journals, research results, and other references. This method is also used to reveal various legal documents related to legal protection arrangements for Indonesian minority groups. This can be seen from the various procedures and procedures. But just relying on the rule of law is not enough, we need our policies. Belief as citizens who live in the midst of diversity to promote tolerance and avoid discrimination. The government needs to prioritize a rights-based approach in the process of formulating programs and policies, in line with efforts to protect and enforce the rights of minority and marginalized groups based on the Pancasila philosophy. Keywords: Human Rights, minority groups, equality before the law Keywords: Human Rights, minority groups, equality before the law